Detailed kinetic mechanism of thermal decomposition of furyl radicals: Theoretical insights. (15th March 2021) - D.-T. Nguyen, Thi; Pham, Nhung; V.-T. Mai, Tam; Minh Nguyen, Hoang; Huynh, Lam K.
Graphical abstract: Highlights: The detailed kinetic mechanism is theoretically reported in 500–2000 K and 1–76000 Torr. Mechanistic inconsistency and incompleteness in previous studies are resolved. Unimolecular decomposition dominates ( 2-furyl ↔ 3-furyl) isomerization. Well-skipping reactions are observed at high temperatures and/or low pressures. Abstract: This study presents the detailed kinetic mechanism of the thermal decomposition of furyl radicals, which play an essential role in the production of the second-generation lignocellulosic biofuels. In particular, the accurate composite method W1U was used to explore the main reaction pathways on which the temperature- and pressure-dependent kinetic behaviors were analyzed in the range of 500–2000 K and 1–76000 Torr using a complementary deterministic/stochastic Rice-Ramsperger-Kassel-Marcus based master equation rate model. Corrections of tunneling and hindered internal rotation treatments were included in the rate model. Detailed kinetic analyses, including time-resolved species profile and flux analysis, reveal that: ( i ) the decomposition pathways are more favorable than the ( 2-furyl ↔ 3-furyl) isomerization; and ( ii ) the well-skipping reactions, accounting for the formation of the products in a shorter time scale, are observed at high temperature and/or low pressure. The calculated thermodynamic and kinetic parameters are in good agreement with literature data; thus, the reported detailed kinetic mechanism can be confidently used to investigate furyl-related systems in different conditions. Also, among the selected composite methods, CBS-QB3 and CBS-APNO have shown to be cost-effective methods in replacing the higher level W1U for constructing the reaction mechanisms for larger similar systems.